Controlling Superstructure-Property Relationships via Critical Casimir Assembly of Quantum Dots - Marino, Emanuele; Balazs, Daniel M.; Crisp, Ryan; Hermida-Merino, Daniel; Loi, Maria A.; Kodger, Thomas E.; Schall, Peter (Journal of Physical Chemistry C, 2019)
The assembly of colloidal quantum dots (QDs) into dense superstructures holds great promise for the development of novel optoelectronic devices. Several assembly techniques have been explored; however, achieving direct and precise control over the interparticle potential that controls the assembly has proven to be challenging. Here, we exploit the application of critical Casimir forces to drive the growth of QDs into superstructures. We show that the exquisite temperature-dependence of the critical Casimir potential offers new opportunities to control the assembly process and morphology of the resulting QD superstructures. The direct assembly control allows us to elucidate the relation between structural, optical, and conductive properties of the critical Casimir-grown QD superstructures. We find that the choice of the temperature setting the interparticle potential plays a central role in maximizing charge percolation across QD thin-films. These results open up new directions for controlling the assembly of nanostructures and their optoelectronic properties.